Inertização de minerodutos para mitigação de sua corrosão interna - Ayron Silva Guimarães Torres (2021)
The transport capacity of the pipelines is related to the internal roughness of the pipeline. Thus, the application of corrosion protection methods is of fundamental importance, both in the operational phase and in times of temporary shutdown. In addition, corrosion also affects the life of the pipeline. The second Samarco’s slurry pipeline was inertized with nitrogen gas in 2015, using the ABNT NBR 15280-2 standard as reference. Chemical, mineralogical and microstructural analyzes were conducted on samples of materials removed from the inside of the duct by foam pigs, in 2017, in order to identify and characterize the corrosion product. The most striking phase found was magnetite, with botrioidal morphology, formed by the oxidation of steel in the pipeline. In 2019, the slurry pipeline was reactivated and later inspected with smart pigs, ultrasound and MFL (Magnetic Flux Leakage) technologies. In these inspections it was found that the corroded regions are more concentrated in the initial kilometers of the sections, where greater depths of corrosion were also observed, as well as higher corrosion and erosion rates, which shows the greater influence of the operational phase in the development of the corrosive process and pipeline wear. Furthermore, most of the corroded regions reported by the pig have a low percentage of depth, varying between 10% and 33%, with more than 98% of these regions having depths less than or equal to 15%, which shows that the corrosive process is not developed substantially. Thus, the application of the inertization process in long-distance pipelines proved to be feasible for long periods of time. However, this work suggests improvements in the inertization process to make it more robust.